Children's data journeys beyond the 'supply chain': co-curating flows and frictions. Issue 1 (February 2019) - Swist, Teresa; Collin, Philippa; Third, Amanda
This article explores the flows and frictions of children's data in the digital age, and how datafication becomes another way of knowing and governing children. There is an urgent need to better understand such digital orientations, who controls them, and how children's agency becomes enabled and constrained. In this article, we argue that a child rights framework operates to surface the tensions and stumbling blocks at play in the ostensibly seamless circulation of children's data through the socio-technical assemblages of corporate, government and university organisations. Smooth flows of data become problematised when we explore children's data journeys and associated frictions with data. This demonstrates the importance of moving beyond existing attempts to better steer children and their data, towards the much more difficult role of co-curating the social, spatial and material supports required to enhance their agency in the digital age.